PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Widyaningrum, Retno; Khudlori, Ahmad (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2024)
Learning mathematics is very important in everyday life. However, there are still many obstacles in the mathematics learning process, one of which is obstacles to solving mathematical problems. In an effort to overcome this, researchers conducted research on mathematics learning using the Realistic Mathematics Education (RME) approach. This research aims to determine the implementation of the Realistic Mathematics Education (RME) approach, determine students' mathematical problem solving abilities after implementing the Realistic Mathematics Education (RME) approach, and determine the effectiveness of the Realistic Mathematics Education (RME) approach to improve mathematical problem solving abilities. This research uses a quantitative research approach with a quasi-experimental type of research. Data collection was carried out by observation and tests. The sample in this study used a cluster random sampling technique. The research data was processed and hypothesis testing was carried out in the form of the Independent t Test and the N-Gain Test. The results of this research are (1) the Realistic Mathematics Education (RME) approach at the first meeting was 83% and 91% was implemented at the second meeting. (2) Students' mathematical problem solving abilities after being given the Realistic Mathematics Education (RME) approach obtained an average score of 89.43. (3) The independent t test hypothesis shows that there are differences in mathematical problem solving abilities in the control and experimental classes. In the N-Gain test the control class obtained a score of 28% and the experimental class 64%. So it can be concluded that the Realistic Mathematics Education (RME) Model is quite effective in improving students' mathematical problem solving abilities.